Epidemiologic patterns of Ross River Virus disease in Queensland, Australia, 2001-2011 - Yu, W.; Mengersen, K.; Dale, P.; Mackenzie, John; Toloo, G.; Wang, X.; Tong, S. (The American Society of Tropical Medicine and Hygiene, 2014)
Ross River virus (RRV) infection is a debilitating disease that has a significant impact on populationhealth, economic productivity, and tourism in Australia. This study examined epidemiologic patterns of RRV disease in Queensland, Australia, during January 2001–December 2011 at a statistical local area level. Spatio-temporal analyses were used to identify the patterns of the disease distribution over time stratified by age, sex, and space. The results show that the mean annual incidence was 54 per 100,000 persons, with a male:female ratio of 1:1.1. Two space-time clusters were identified: the areas adjacent to Townsville, on the eastern coast of Queensland, and the southeast areas. Thus, although public health intervention should be considered across all areas in which RRV occurs, it should specifically focus on highrisk regions, particularly during summer and autumn to reduce the social and economic impacts of RRV infection.